Islam and nation separatist rebellion in Aceh, Indonesia - Aspinall, Edward (Studies in Asian security, 2009)
Islam and Nation is a tour de force in the study of nationalist politics. It will be of great interest to readers concerned about Southeast Asia, Islamic politics, ethnic conflict and nationalism everywhere.